The effects of age and training prescription on the acute responses to training in young Italian rugby union players - Spinabelli, S.; Nigro, F.; Marcora, S. M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Questionnaires and scales are often used to monitor training loads and training effects in elite sports (1). The purpose of the present research was to understand the moderating effect of age on the internal training load and acute responses to two different training prescriptions in young high-level rugby union players.